Improving Personal Financial Management through Financial Technology, Financial Capability, and Spiritual Intelligence as Intervening Variable - Erlina Dewi Endah Amaliyah; Bayu Setyo Nugroho (Politeknik Negeri Semarang, 2022)
In this millennial era, we often hear the term of sandwich generation. Therefore, they are required to be able to manage their finance very well, so that all needs can be met. Not only for the sandwich generation, everyone should be able to manage their finance well to achieve financial freedom. There are various ways fo managing finance today, for examples using financial technology (FT), using financial education and being directly involved in financial activities (FC). In addition, spiritual intelligence (SI) or an attitude of self-introspection and self-control is also needed to maximized personal financial management. This study aims to find out how to improve personal financial management through FT, FC, and SI factors. The samples are 100 people in productive age who lived in Central Java. The data collection method used a combination of accidental and purposive sampling. Research questionnaires distributing through social media then analized using SEM PLS. The result show that FT and SI have an effect on PFM. It means that the perceived usefulness and perceive ease of use of using FT, self-introspection and self-control can affect a person’s ability to manage their finance. SI also has a quasi or partial indirect effect on PFM. However, FC have no effect on PFM and SI. Direct involvement in financial activities doesn’t affect a person’s ability to manage their finances. It also doesn’t affect the attitude of self-introspection and self-control. This shows that direct involvement in financial activities doesn’t guarantee a person’s ability to manage their finances